PEMBUKTIAN TERHADAP KEJAHATAN KESUSILAAN DALAM QANUN TENTANG JINAYAT DAN HUKUM ACARA JINAYAT - Heru Susetyo; N. Oneng Nurul Bariyah (Jurnal Hukum PRIORIS, 2021)
Proof of a crime in the Indonesian criminal justice system is part of the criminal procedure or formal law. In Islamic law, the proof is part of the procedural law, aka fiqh murafa'at. If the study of material Islamic criminal law (jinayat) has developed very widely, on the other hand, the study of murafa'at fiqh in Indonesia is not very broad. Moreover, in practice in Indonesia fiqh murafa'at can only be seen in its application to the Syar'iyah Court in Aceh, which does apply Islamic law not only in the civil field (muamalah) but also in the criminal area (jinayat). The Jinayat Procedural Law at the Aceh Syar'iyah Court is regulated by Aceh Qanun No. 7 of 2013. This study examines the application of the procedural law of jinayat at the Syar'iyah Court in Aceh, especially in the chapter on evidence. This proof is also limited to only three moral offenses, namely adultery, seclusion, and ikhtilath, which are indeed part of the offense (jarimah) regulated in Aceh Qanun No. 6 of 2014 concerning Jinayat Law. The research location is the Aceh Syar'iyah Court and the Aceh Besar Syar'iyah Court in Jantho. The analytical knife used is maqashid shari'ah, the theory of legal certainty and the presumption of innocence. The findings of this study are the evidence in the case of a crime (jarimah) of decency at the Syar'iyah Court in Aceh is a modification of the murafa'at fiqh that exists in the Islamic treasury, which is adapted to the context of national criminal procedural law and the socio-political and cultural situation of Indonesia. Aspects of confession and oath are highly emphasized in proving moral offenses, more so than witness statements, expert statements, instructions, and letters recognized in the Criminal Procedure Code. Therefore, it can be concluded that the procedural law of jinayat in the Syar'iyah Court is sufficient to guarantee justice and legal certainty. Still, it needs to be developed and harmonized with the development of science and technology and the national criminal procedure law.Keywords: proof; decency; shariah court; Aceh; Jinayat